Analisis Kondisi Sarana dan Prasarana Kantor Pada PT. Sumber Artha Barokah - Ahmad Azzam Yuhdiwanto; Christian Wiradendi Wolor; Marsofiyati Marsofiyati (Jurnal Kajian dan Penelitian Umum, 2023)
Office means and infrastructure such as office equipment and work space are things that need to be considered in terms of their condition. If the condition of office means and infrastructure is not in good condition, it will cause damage which will disrupt work activities for employees. The aim of this research is to determine the condition of office means and infrastructure at PT. Sumber Artha Barokah which includes how to maintain the condition of means and infrastructure as well as setting schedules for maintaining the condition of office means and infrastructure. This research uses a qualitative approach by analyzing the problems found. Qualitative research is based on primary data and secondary data. Primary data begins with observation, continues with interviews, and ends with documentation. Meanwhile, secondary data was obtained through books, previous research, and articles related to research. From the research results, it can be seen that PT. Sumber Artha Barokah already has a fairly good condition of means and infrastructure, but not all office means and infrastructure receive attention in terms of their quality. This can be seen from the lack of maintenance on production parts and office machines which are only repaired when damage occurs.